Phase Transformation And Force-Deflection Responses Of Niti Archwire For Bracket Assembly In Orthodontic Treatment - Razali, Muhammad Fauzinizam (2018)
NiTi archwires are used widely during the early stage of orthodontic treatment due to its superelastic and biocompatibility properties. Even though the superelastic NiTi archwires are always preferred in most orthodontic treatments, the evolution of phase transformation and force-deflection behaviour of this wire subjected to bend in the bracket system is still uncertain. Since changes in bending setting are frequently encountered during levelling, the extent of wire deformation and binding friction at the wire-bracket interface would alter the force-deflection behaviour and subsequently defies the optimal force criteria. This study investigated the evolution of phase transformation and forces released by NiTi archwire during orthodontic levelling treatment. For this purpose, a three-dimensional finite-element model of superelastic NiTi wire bends in three-bracket configurations was developed by employing a user material subroutine of superelasticity and contact interaction. The friction coefficient required to define the contact between the wire and stainless steel bracket was obtained from a sliding test. The competency of the bending model was examined by comparing the predicted force-deflection curve with the experimental results. The work further advanced the current knowledge on the influence of binding towards the force-deflection behaviour of NiTi wire by performing a quantitative study at two levelling conditions; bending at different levelling settings (inter-bracket distance, wire deflection and oral temperature) and bending with the presence of different bracket materials (friction coefficient at contact locations were varied from 0.1 to 0.5. During bending, only a small section of the wire length underwent austenite to martensite transformation, leaving the rest of the length substantially undeformed. The wire activated to 2.0 mm produced the maximum stress on the stress plateau, implying that the NiTi wire was deformed by stress-induced martensitic transformation. The wire activated to 3.0 mm and 4.0 mm essentially produced the maximum stress on the elastic line of martensite. The generation of binding at the bracket edges significantly elevated the maximum force and the slope of the deactivation curve, whilst diminished the minimum force values. The greatest binding of 8.33 N and 3.72 N was generated by the 0.40 × 0.56-mm and 0.4-mm archwires at the maximum deflection (4.0 mm) and temperature readings (46°C), and at the minimum inter-bracket distance (7.0 mm). For the case of large tooth displacement (4.0 mm), the 0.4-mm archwire delivered force in between 0.13 N to 0.73 N, which are within the optimal force range. The developed regression model can be used to predict the force-deflection of NiTi wire for the studied bracket system. Additionally, the archwires coupled with the ceramic brackets (≥ 0.4) produced zero force magnitude at the onset of the deactivation cycle, thus inhibited further tooth movement.